Hypereosinophilia Syndrome: Myriad Presentation—A Case Report - Patel, Mansi; Shah, Divit; Patel, Sujal; Acharya, Sourya; Kumar, Sunil; Shukla, Samarth (Journal of Health and Allied Sciences NU, 2023)
Hypereosinophilic syndrome is a myeloproliferative disorder that is distinguished with the presence of eosinophilia, which is an absolute eosinophil level of more than 1500/µL for no less than 6 months, no recognized cause for eosinophilia, and clear organ involvement characteristics. But, in some cases where patients require therapy to decrease eosinophil counts due to severe symptoms, a lower time period of hypereosinophilic is also admissible. In this case series, we have included three cases in which first case presented with the features of diarrhea, nausea, and decreased appetite who underwent colonoscopy and was diagnosed as a case of eosinophilic colitis. The second patient was a female came with abdominal pain and burning micturition, who was having eosinophilia on blood count examination and was diagnosed as a case of eosinophilic cystitis. Third case was young female who was diagnosed as eosinophilic endocarditis on two-dimensional echocardiography having dyspnea and rash and high eosinophil count on blood smear. All the three patients were started on steroids, who recovered well with medication and were discharged for follow-up after 7 days with complete blood count.
Keywords: hypereosinophilia; gastroenteritis; cystitis; endocarditis